2006
DOI: 10.1126/science.1126548
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Glycoprotein B from Herpes Simplex Virus 1

Abstract: Glycoprotein B (gB) is the most conserved component of the complex cell-entry machinery of herpes viruses. A crystal structure of the gB ectodomain from herpes simplex virus type 1 reveals a multidomain trimer with unexpected homology to glycoprotein G from vesicular stomatitis virus (VSV G). An a-helical coiled-coil core relates gB to class I viral membrane fusion glycoproteins; two extended b hairpins with hydrophobic tips, homologous to fusion peptides in VSV G, relate gB to class II fusion proteins. Member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
810
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(832 citation statements)
references
References 30 publications
19
810
2
1
Order By: Relevance
“…Mutations in the cytoplasmic tail of gB enhance cell-cell fusion of HSV-1 isolates (38-40) and also enhance cell-cell fusion of HSV glycoproteins in plasmid-based fusion assays (20,41,42) in a manner similar to that seen for mutations in the cytoplasmic tail of the fusion protein of HIV, gp120/gp41 (43). Furthermore, the recently solved crystal structure of HSV-1 gB lacking the transmembrane domain and cytoplasmic tail revealed a striking homology to the structure of vesicular stomatitis virus G fusion protein (15). Both gp120/gp41 and G proteins are active during Phase III of fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the cytoplasmic tail of gB enhance cell-cell fusion of HSV-1 isolates (38-40) and also enhance cell-cell fusion of HSV glycoproteins in plasmid-based fusion assays (20,41,42) in a manner similar to that seen for mutations in the cytoplasmic tail of the fusion protein of HIV, gp120/gp41 (43). Furthermore, the recently solved crystal structure of HSV-1 gB lacking the transmembrane domain and cytoplasmic tail revealed a striking homology to the structure of vesicular stomatitis virus G fusion protein (15). Both gp120/gp41 and G proteins are active during Phase III of fusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, their exact role in the fusion mechanism has yet to be elucidated. There are two models for fusion: the regulatory/structural model, where one glycoprotein serves as a regulator or a support for the fusogenic activity of the other (14,15); and the sequential model, where each glycoprotein functions at a different stage in the fusion process (7). If the sequential model is correct, it may be possible to separate the function of the glycoproteins in fusion through assays that detect a fusion intermediate, such as hemifusion.…”
mentioning
confidence: 99%
“…The structure of herpes simplex virus 1 (HSV1, a double-stranded DNA virus) glycoprotein gB [57] was published at the same time as that of G th post-fusion state. Comparison of the two structures revealed that their folds are the same and that they have a common evolutionary origin that could not be detected by looking at the amino acid sequences (Fig.…”
Section: An Unexpected Homologymentioning
confidence: 99%
“…(1) the PMI of extended conformation internal fusion peptides postulated from structures of dengue, Semliki forest, herpes, and vesicular stomatitis viral fusion proteins; (2) the PMI of helical influenza fusion peptide determined from electron spin resonance experiments; and (3) a PMI model based on the HFP-F8W fluorescence measurements (37,61,62,(93)(94)(95)(96). However, the locations of lipids in the perturbed leaflet in the PMI model are not clear.…”
Section: Insertion Modelsmentioning
confidence: 99%